2014
DOI: 10.1080/01446193.2014.911931
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between early constructor involvement in project decision-making and the efficacy of health and safety risk control

Abstract: Exploring the link between early constructor involvement in project decision-making and the efficacy of health and safety risk control

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…For example, there was evidence to suggest that investigators within the participating organizations are presently prompted to focus on factors surrounding the immediate context of the incident and then individual error. This finding is consistent with previous research surrounding construction accident causation (e.g., Lingard, Pirzadeh, Blismas, Wakefield, & Kleiner, ; Manu et al., ; Wang et al., ) that reinforces the existing focus on mid‐ to lower‐level actors and factors (e.g., company, management, and staff levels). Overall, the finding that construction accident investigations focus on mid to lower levels of the RMF, although not surprising given the limitations of the embedded Swiss cheese (Reason, 1997) approach to accident causation within construction (Hopkins, ; Woolley et al., under review), highlights the need to move beyond the individual and the organization.…”
Section: Discussionsupporting
confidence: 91%
“…For example, there was evidence to suggest that investigators within the participating organizations are presently prompted to focus on factors surrounding the immediate context of the incident and then individual error. This finding is consistent with previous research surrounding construction accident causation (e.g., Lingard, Pirzadeh, Blismas, Wakefield, & Kleiner, ; Manu et al., ; Wang et al., ) that reinforces the existing focus on mid‐ to lower‐level actors and factors (e.g., company, management, and staff levels). Overall, the finding that construction accident investigations focus on mid to lower levels of the RMF, although not surprising given the limitations of the embedded Swiss cheese (Reason, 1997) approach to accident causation within construction (Hopkins, ; Woolley et al., under review), highlights the need to move beyond the individual and the organization.…”
Section: Discussionsupporting
confidence: 91%
“…For example, safety-related communications are vital to include every individual in a construction crew to ensure strong safety performance [ 79 , 80 ]. It is better that the communication is involved in pre-construction decision-making [ 81 ]. Kulkarni also indicated that the workforce in the construction sector was the most vulnerable because employment was permanently temporary, the employer and employee relationship was very fragile and most of the time short-lived and the work had inherent risk to life and limb due to lack of safety, health and welfare facilities, coupled with uncertain working hours [ 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atkinson and Westall (2010) also note that, even in more integrated projects utilising a design and construction delivery approach, the design of the product to be constructed is often outsourced to a specialist team of professional designers and positive OH&S outcomes are not guaranteed. Lingard et al (2014) examined the quality of OH&S risk control outcomes associated with decisions made during the design stage of construction projects and found evidence that more effective technological forms of risk control (e.g. elimination, substitution and engineering controls) were more likely to be implemented when people with construction process knowledge were involved in decision-making.…”
Section: Designing For Ohandsmentioning
confidence: 99%